2022
DOI: 10.3390/foods11131892
|View full text |Cite
|
Sign up to set email alerts
|

Texture Characteristics of Sea Buckthorn (Hippophae rhamnoides) Jelly for the Elderly Based on the Gelling Agent

Abstract: The aim of this study was to identify the nutritional components of sea buckthorn berries and to evaluate the hardness control of the elderly with mastication difficulties using various types and concentrations of gelling agents in the preparation of sea buckthorn jelly. As a result, sea buckthorn berry comprised various bioactive nutrients, including minerals, essential fatty acids, and antioxidative and antidiabetic substances. In addition, jelly added with 3.01% guar gum, 5.74% xanthan gum, and 11.38% locus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Each filtrate (40 μL) was transferred to a 10 mL screw cap tube, and then, a 10-fold diluted folin-ciocalteau reagent (800 μL) was added, mixed well, and left in a dark place for 5 min [ 37 ]. A 7% sodium carbonate aqueous solution (800 μL) was added thereto; the remaining volume was filled with distilled water (DW; 360 μL), mixed well, and left in a dark place at room temperature for 2 h. Its absorbance was measured at 760 nm using a UV visible spectrophotometer (T60UV, PG instruments Ltd., Lutterworth, UK).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each filtrate (40 μL) was transferred to a 10 mL screw cap tube, and then, a 10-fold diluted folin-ciocalteau reagent (800 μL) was added, mixed well, and left in a dark place for 5 min [ 37 ]. A 7% sodium carbonate aqueous solution (800 μL) was added thereto; the remaining volume was filled with distilled water (DW; 360 μL), mixed well, and left in a dark place at room temperature for 2 h. Its absorbance was measured at 760 nm using a UV visible spectrophotometer (T60UV, PG instruments Ltd., Lutterworth, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Each filtrate (0.5 mL) was mixed with 95% ethanol (1.5 mL), 10% aluminum chloride hexahydrate (0.1 mL), 1 M potassium acetate (0.1 mL), and DW (2.8 mL) and left at room temperature for 40 min in a dark place [ 37 ]. Its absorbance was measured at 415 nm with a UV visible spectrophotometer (T60UV, PG instruments Ltd., Lutterworth, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 H. rhamnoides L. was first recorded in the Chinese Pharmacopoeia in 1977, and had been included in each edition of Chinese Pharmacopoeia with the functions of invigorating spleen and eliminating food, relieving cough and eliminating phlegm, promoting blood circulation, and dispersing blood stasis. 4 H. rhamnoides L. has been categorized as a "medicine food homology" fruit by China's National Health Commission for both nutritional and medicinal purposes. 5 In the last few decades, an increasing amount of various studies showed that the edible and medicinal H. rhamnoides L. possessed different types of chemical components and multiple pharmacological activities.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, parsnip has a hard texture like other root vegetables, making it difficult for the elderly to chew. According to the previous research (Kim & Iida, 2022), it is emphasised that the soft texture of food is an important factor in increasing the balanced nutrient intake of the elderly, so it is used as an attribute of root vegetable quality evaluation for the elderly. One of these methods is the enzyme‐injection method.…”
Section: Introductionmentioning
confidence: 99%